Leverage and Executive Pay-Performance of The Indonesian Family Firms - Aang Kunaifi; Ninditya Nareswari; Byz Risyad (ADI Publisher, 2020)
This study aims to investigate the impact of firm performance on executive compensation. This study also examines the moderating role of leverage on the firm performance and executive pay-performance relationship. Used data panel regression as a method, this study showed that firm performance had a positive impact on executive compensation. This paper also showed that leverage weakens the pay-performance relationship. These results indicate that creditors prefer to assess family firm performance based on the risk rather than accounting performance. Higher leverage illustrated a high risk. The firm with high risk indicated poor executive performance. As a result, compensation will be lower.